Reduction of CMOS Image Sensor Read Noise to Enable Photon Counting - Michael Guidash; Jiaju Ma; Thomas Vogelsang; Jay Endsley (Sensors, 2016)
Recent activity in photon counting CMOS image sensors (CIS) has been directed to reduction of read noise. Many approaches and methods have been reported. This work is focused on providing sub 1 e− read noise by design and operation of the binary and small signal readout of photon counting CIS. Compensation of transfer gate feed-through was used to provide substantially reduced CDS time and source follower (SF) bandwidth. SF read noise was reduced by a factor of 3 with this method. This method can be applied broadly to CIS devices to reduce the read noise for small signals to enable use as a photon counting sensor.